Sinking States, Shifting Boundaries: Sea-Level Rise, Statehood and Maritime Entitlements After the ILC’s 2025 Final Report – Implications for Africa and Nigeria - Miebaka Nabiebu; Alobo Eni Eja; Edem Essien Udoaka; Gabriel Etim-Ben Inyang (Pinisi Journal of Social Science, 2026)
The International Law Commission (ILC) concluded its landmark study on sea level rise in relation to international law at its seventy sixth session in 2025, adopting a final report that addresses three interconnected sub topics: the law of the sea, the continuity of statehood, and the protection of persons affected by sea level rise. This paper analyses the ILC’s final report and the subsequent clarifying advisory opinion of the International Court of Justice (ICJ) issued on 23 July 2025, which together represent the most authoritative statement to date on how international law should respond to the existential challenges posed by rising seas. The paper argues that while the ILC’s work and the ICJ’s opinion have moved the legal framework decisively towards baseline stability and a presumption of state continuity, critical doctrinal gaps remain – particularly regarding the normative status of the “presumption” of statehood and the practical implementation of fixed baselines in developing regions. Using Africa and Nigeria as a case study, the paper demonstrates that low lying coastal states and communities face not only physical submersion but a layered crisis of maritime entitlement erosion, internal displacement, and cross border resource conflict. The 2025 legal developments offer unprecedented support for preserving maritime zones and statehood, but translating these principles into enforceable rights requires urgent regional cooperation, legislative reform, and investment in coastal mapping and digital governance. The paper concludes with concrete recommendations for African coastal states, with special attention to Nigeria’s Niger Delta, to operationalise the ILC’s findings and secure their maritime futures.